Relationship between secondary school libraries, the media and social problems: bibliographic research - Infante-Fernández, Lara María; Romo-Fernández, Luz María; Faba-Pérez, Cristina (Revista General de Información y Documentación, 2025)
An analysis is made of the interrelationship connecting Spanish school libraries, the use of social media, and the different social issues that form part of secondary education pupils' curriculum in Spain, with especial emphasis on issues related to vulnerability and social awareness. The analysis was carried out through a bibliographic review of current legislation, regulations, and strategic plans, as well as by retrieving scientific articles, reports, and conference papers from searches of different databases. This yielded a bibliographic corpus of 81 documents to which a detailed in-depth study of keyword repetition frequency was applied. The result was a final definitive set of documents providing an overview of the state of the question, with keywords such as 'migrant', 'refugee', 'social media', and 'school library' being among the top terms found in them.
Keywords: Secondary education; school libraries; social problems; social media; Literature review